PENGARUH TERAPI TERAPI BEKAM KERING TERHADAP INTENSITAS NYERI PASIEN DENGAN LOW BACK PAIN - Ramananda, Gede Adi (Coping: Community of Publishing in Nursing, 2014)
Low Back Pain is often encountered complain in daily life. Low back pain is pain in the back between the bottom corner of the costal (rib) to the lumbosacral (around the tail bone). Conservative management of low back pain is usually addressed in two ways: pharmacological and non-pharmacological. One of non-pharmacologic therapy is a complementary therapy that dry cupping therapy. This study aims to determine the effect of dry cupping therapy on pain intensity in patients with low back pain (low back pain) in the Latu Usadha Private  Practice NursingAbiansemal. The method is one group pretest-posttest design without control group , non-probability sampling technique that is incidental sampling sampling with a sample of 23 people. Results of data analysis using the Wilcoxon test with ? = 0.05 showed that the value of significan (p) is 0.000, which means p <0.05 with an error rate of 5%, then Ho (zero) is rejected which means that there is the effect of the dry cupping therapy pain intensity scale in patients with low back pain. . It can be concluded that the dry cupping therapy reduce low back pain by 95%
Keywords: Dry Cupping Therapy; Pain Intensity; Low Back Pain